SOCIAL PARTNERSHIP FOR VOCATIONAL EDUCATION DEVELOPMENT IN DIGITAL ERA OF VOCATIONAL COLLEGES UNDER ZHEJIANG PROVINCE - Yu, Jiang; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) to propose the framework of social partnership for vocational education development in digital era of Vocational Colleges under Zhejiang Province; and (2) to develop the future wheels of social partnership for vocational education development in digital era of Vocational Colleges under Zhejiang Province. A qualitative approach utilizing the Delphi technique was employed, involving 20 key informants from diverse vocational education backgrounds. Their insights critically informed the suggested social partnership framework. Data were collected and then encoded and categorized using both the Delphi technique and the future wheels study. Instruments used for data collection included an open-ended interview form and a five-point rating scale questionnaire. Data analysis methods incorporated mode, median, Inter Quartile Range, and content analysis. The research revealed that: (1) a framework that accentuates dynamic interactions across micro, meso, and macro levels of social partnerships was proposed. Four dimensions were pinpointed at the micro level, five dimensions at the meso level, and three dimensions at the macro level. These dimensions not only reflect broader socio-political and economic influences but also underscore the significance of inclusive vocational education policies; and (2) future wheels for vocational education development in the digital era, tailored for vocational colleges in Zhejiang Province, were derived from expert evaluations of emerging trends.